Grafomotricidad y su incidencia en el desarrollo de la motricidad fina a estudiante de la Escuela de Educación Básica 24 de Mayo, de la Parroquia San Juan, Cantón Puebloviejo, Provincia Los Ríos 2021-2022 - Aguirre Mora, Nancy Gissella (2022)
The objective of the present work is to verify the importance of graphomotricity in the child's learning, in the acquisition of skills necessary to express himself through written signs, through exercises that allow greater control of the forearm, wrist, hand and, above all, the fingers; In this way, the child will develop fine motor skills and will control the movements of the hands more and more, developing their skills and abilities, allowing the child to draw the letters more easily. Graphomotricity, in its role as a promoter of significant learning in school education, stimulates the development of fine motor skills in graphomotor processes through the development of specific activities, as indicated in the course of this document; activities that are applied with students of the school level of the basic education school "May 24". It is important to remember that graphomotricity is a phase prior to writing since it involves training to carry out basic movements that are part of the correct directionality and tracing of letters. The term graphomotricity at the initial level is essentially a motor act that aims to educate and correct the execution of the basic movements involved in writing, fine motor skills are all the movements of the fingers and hands since it involves training for the realization of basic movements that are part of the correct directionality and tracing of the letters. These activities are aimed at achieving graphomotor control of the graphic lines, so that the child learns the basic movements and avoids useless movements. They also allow to prevent later writing anomalies such as inverted turns, direction, pencil pressure, etc.